RANCANGAN D-OPTIMAL UNTUK OPTIMASI VARIABEL RESPON PADA METODE PERMUKAAN RESPON ORDE DUA - , FATMAH BUDIANI ARINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Response Surface Method is a method used to find the relationship between the independent variables and the dependent variable then optimize the dependent variable. In general, response surface method consists of designing experiments, modeling influential variable, and perform optimization. Response surface methods have many experimental designs, classic designs such as the Central Composite Design (CCD), Box-Behnken design (BBD) and Computer Generated as D-Optimal Design. Optimal design requires little experiment so as to minimize the cost of the experiment. D-Optimal criteria are used to minimize the variance of the parameter estimates by maximizing the determinant of the information matrix determinant. The selection of the points of the design depends on the model chosen and the desired number of experimental units. In this thesis, D-Optimal criteria applied to the data on the total lipid of microalgae Chroococcus Sp, 3 independent variables are based on the cell density, the composition of nitrogen, phosphorus composition. it can be concluded at the cell desdity=3.206026, composition of nitrogen=0.264478 g/l and phosphorus composition=0.396292 g/l will result in the total lipid optimum 7.159689%.